2023
DOI: 10.1002/mnfr.202300005
|View full text |Cite
|
Sign up to set email alerts
|

Milk Exosomes from Gestational Diabetes Mellitus (GDM) and Healthy Parturient Exhibit Differential miRNAs Profiles and Distinct Regulatory Bioactivity on Hepatocyte Proliferation

Abstract: ScopeExosomes, a novel type of bioactive component in human milk (HM), affect infant development, growth, and health. Recent studies indicate that HM exosomes and miRNAs relate to gestational diabetes mellitus (GDM). However, the miRNAs profiles and functionalities of HM exosomes from GDM parturient remain unclear. This study aims to compare the differential miRNAs in HM exosomes from GDM and healthy parturient, and investigate the HM exosomes bioactivities in regulating hepatocyte proliferation and insulin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Bovine milk exosomes increased intracellular miR-146a and miR-155 levels and inhibited the expression levels of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1) genes, but promoted HO-1 protein expression [121]. Consistent with the results of other studies, the MDA levels were increased by camel milk exosomes in male albino rats [71]. The mechanisms underlying these oxidative stresses involve Wnt signaling, which has been proposed as the target pathway upregulated by milk exosomes [124].…”
Section: Studies On Anti-inflammatory and Antioxidant Action Of Milk ...supporting
confidence: 86%
See 1 more Smart Citation
“…Bovine milk exosomes increased intracellular miR-146a and miR-155 levels and inhibited the expression levels of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1) genes, but promoted HO-1 protein expression [121]. Consistent with the results of other studies, the MDA levels were increased by camel milk exosomes in male albino rats [71]. The mechanisms underlying these oxidative stresses involve Wnt signaling, which has been proposed as the target pathway upregulated by milk exosomes [124].…”
Section: Studies On Anti-inflammatory and Antioxidant Action Of Milk ...supporting
confidence: 86%
“…The content of individual miRNAs and other non-coding RNA in milk exosomes depends on the mother's diet [67]. Milk exosomes from mothers with type 1 diabetes have also been investigated, showing aberrant levels of miRNAs [68][69][70] as well as exhibiting distinct regulatory bioactivities on hepatocyte proliferation, with the inhibition of hepatocyte proliferation by downregulating mTOR via exosomal miR-101-3p delivery [71]. Milk exosomes from obese mothers also have altered miRNA composition, whose target genes are associated with neurological diseases and psychological disorders, indicating an impact on breastfed infants [72].…”
Section: Biological Activities Of Milk Exosomesmentioning
confidence: 99%
“…Human milk exosomes from gestational diabetes mellitus (GDM) and healthy parturients showed distinct regulatory bioactivities in both HepG2 cell cultures and, in vivo, in the liver of Balb/c mice. The profile of GDM exosomes has been related to natural loading by miR-101-3p [34]. Previous studies confirmed that the target gene of miR-101-3p is mTOR.…”
Section: Bioavailability Of Mature Mirnas In the Digestive Systemmentioning
confidence: 92%
“…Many short RNAs are undescribed and, beyond as an interest as biomarkers, new regulatory processes may be The recovery of exosomes is influenced by the procedure of sampling (Figure 1C) and a systematic centrifugation step of the milk before storage has been proposed in order to remove cells and debris [33]. A minimal volume of 1.5 mL whole milk has been used to purify exosomes [19], which is a technical lock, up to higher volumes like 20 mL [34].…”
Section: Rna Content and Mature Mirna Diversitymentioning
confidence: 99%